PENGARUH CAPITAL ADEQUACY RATIO(CAR), RETURN ON ASSETS(ROA), DANA PIHAK KETIGA(DPK), NON PERFORMING LOAN(NPL) DAN NET INTEREST MARGIN(NIM) TERHADAP PENYALURAN KREDIT PERBANKAN (Studi Pada Bank Umum yang terdaftar di BEI periode 2009-2013) - Sekar Primasari, Nathasa; Mahfud, M. Kholiq (Diponegoro Journal of Management, 2015)
The purpose of this research is to examine the influence of Capital Adequacy Ratio (CAR), ReturnOn Assets (ROA), Third Party Fund (DPK), Non Performing Loan (NPL) and Net Interest Margin(NIM) to distribution of credit in commercial bank. This research used the Commercial Bank which was go public and listed it to Indonesian Stock Exchange. The data that it used at this research came from the annual published financial report of each Commercial Banks.The population in this research was all Commercial Banks that was go public and listed it to Indonesian Stock Exchange during period 2009 through 2013. The amount of population was 35commercial banks. After passed the purposive sampling method, amount of the bank that fulfilled the criteria of sample became 25 commercial banks. The method that used in this research was multiple regression analysis and then used assumption classic test and used hypothesis test that including F-statistic, T-statistic and determination of coefficients (R2).The result of this research was CAR variable influence negatively and not significant to distribution of credit, ROA variable influence negatively and significant to distribution of credit and DPK,NPL and NIM variable influence positively and significant to distribution of credit.